Thermally activated deformation processes in body-centered cubic Cr – How microstructure influences strain-rate sensitivity. (September 2015) - Maier, Verena; Hohenwarter, Anton; Pippan, Reinhard; Kiener, Daniel
Graphical abstract: Abstract : The microstructure dependent deformation behavior of chromium, especially in terms of strain-rate sensitivity (SRS), was studied by means of improved nanoindentation methods as a function of temperature. Cr was investigated in the single crystalline (sx) and ultrafine-grained (ufg) condition. With increasing temperature a decreasing SRS was determined for sx-Cr, while for ufg-Cr a significant increase upon overcoming the critical temperature T c was measured. This is attributed to the increased importance of dislocation–grain boundary interactions, and a change in the dominating deformation behavior.